Real time cross correlator for speed measurement of particle conveying in pneumatic pipeline - Rahmat, Mohd Fua’ad; Chang, Wei Lam (2000)

(untitled)
The idea of signal processing using the cross correlation technique is not new. Since the 1930s, the theory of cross correlation has been in existence, but is was not used by industry until the 1960s, when hardware called the correlator was invented. The cross correlation technique, used to find the velocity of a spinning plastic ball in and in test apparatus to represent the flow of dry powders in a pipe has been developed in this paper. The flow is detected by two axially spaced electrodynamics sensors, where the length of the space is known, and is interfaced with the computer via the AX5412 interface board. This paper focuses on the software development for the AX5412 interface board and for data collection from both sensors, so that the cross correlation technique can manipulate the data. The velocity of the plastic ball can be calculated from the knowledge of the length of space between the sensors with the time shift obtained from the peak of the cross correlation coefficient